2021
DOI: 10.26689/jcnr.v5i3.2112
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of the Effect of the Sandwich Teaching Model on the Learning Outcomes of Nursing Students

Abstract: Objective: To evaluate the effect of the sandwich teaching model on the learning effect of nursing students. Methods: The Chinese and English databases of CNKI, WanFang, Vip, superstar, and PubMed were searched by computer, and the data were analyzed by Rev Man 5.3 software after literature quality evaluation. Results: Meta-analysis showed that the theoretical and operational performance of the nursing students in the sandwich teaching method was better than that of the traditional teaching group. Conclusion: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Starting with nursing problems, we should improve students' team teaching method through “explicit and implicit teaching method” and “vertical and horizontal teaching method”. Through standardized patients (SP) and other means, the introduction of clinical nursing ward round strategy, combined with psychological and emotional training, cultivate students' working ability [ 10 ]. It should be noted that there are differences in students' cognition of teaching quality and effect, especially in autonomous learning ability, nurse patient communication ability, teamwork ability, clinical thinking ability, problem solving ability and stimulating learning interest.…”
Section: Related Workmentioning
confidence: 99%
“…Starting with nursing problems, we should improve students' team teaching method through “explicit and implicit teaching method” and “vertical and horizontal teaching method”. Through standardized patients (SP) and other means, the introduction of clinical nursing ward round strategy, combined with psychological and emotional training, cultivate students' working ability [ 10 ]. It should be noted that there are differences in students' cognition of teaching quality and effect, especially in autonomous learning ability, nurse patient communication ability, teamwork ability, clinical thinking ability, problem solving ability and stimulating learning interest.…”
Section: Related Workmentioning
confidence: 99%
“…It was revealed that Sandwich teaching in medical oncology can effectively promote students' acquisition of knowledge and skills and enhance the teaching effect (Zou and Li, 2021 ). Besides, Sandwich teaching is also demonstrated to improve the theoretical and practical performance of nursing students in different nursing courses (Chen and Li, 2019 ; Hao and Cui, 2021 ). For instance, Sandwich teaching in basic nursing theory teaching was to effectively improve Chinese nursing students' judging, thinking, and core ability, as well as teaching quality (Zhang, 2022 ).…”
Section: Introductionmentioning
confidence: 99%